Cholesterol Transporters of the START Domain Protein Family in Health and Disease 2014
DOI: 10.1007/978-1-4939-1112-7_2
|View full text |Cite
|
Sign up to set email alerts
|

The Steroidogenic Acute Regulatory Protein (StAR)

Abstract: StAR, the Steroidogenic Acute Regulatory protein, was named for its critical role in the acute regulation of steroid hormone biosynthesis in the adrenal and gonads following tropic hormone stimulation. StAR synthesis is required for the first and rate-limiting step in steroid hormone biosynthesis, cholesterol transport into mitochondria. It was a long journey to finding the acute regulator of steroidogenesis, and this chapter provides a historical and personal account of this journey from the perspective of Dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 183 publications
0
10
0
Order By: Relevance
“…It was a positive marker of HER2-positive tumors [ 45 ]. STARD3 was related to the growth and survival of cancer cells amplified by HER2, and has no effect on other cancer cells [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was a positive marker of HER2-positive tumors [ 45 ]. STARD3 was related to the growth and survival of cancer cells amplified by HER2, and has no effect on other cancer cells [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, the transport kinetics measured for the different soluble and isolated START domains fall into a similar range; for instance, STARD4 transports~7 sterols/min (Iaea et al, 2015), whereas CERT/STARD11 transfers 4 ceramides/min (Hanada et al, 2003). The physiology tells a different kinetics, early work on STARD1 indicated that to promote an acute synthesis of steroids in response to trophic hormones, STARD1 must handle several lipid molecules in a very short time (Jefcoate, 2002;Clark & Stocco, 2014). Indeed, STARD1 transfers over 400 molecules of cholesterol/ min (Artemenko et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Gene STARD3 was related to HER2 amplification in Luminal A versus HER2 (+) and HER2 (+) versus TNBC, and it linked to growth and survival of HER2-amplified cancer cells. At the same time, STARD3 gene has no function in other cancer cells [32]. Stefka et al used proteins to find GRB7 gene had an intimate connection with HER2-enriched breast cancer and was amplified in Her2 positive breast cancer.…”
Section: Resultsmentioning
confidence: 99%